Characteristic distribution patterns of perfluoroalkyl substances in soils according to land-use types. (August 2021) - Sim, Wonjin; Park, Heejeong; Yoon, Jeong-Ki; Kim, Ji-In; Oh, Jeong-Eun
Abstract: In this study, a nationwide monitoring of perfluoroalkyl substances (PFAS) in soils was conducted for various land-use types around South Korea, such as industrial complexes, landfills, farmlands, mountains, and woodlands. The ∑15 PFAS concentrations in soil samples ranged from 0.175 to 11.7 ng/g dry weight (dw) (median 2.39 ng/g dw). The soil samples from industrial complexes (0.346–11.7 ng/g dw; median 3.25 ng/g dw) and landfills (0.504–10.4 ng/g dw; median 2.13 ng/g dw) had higher median ∑15 PFAS concentrations than other regions (0.175–3.01 ng/g dw; median 1.15 ng/g dw). In the soil samples from industrial areas, the ∑15 PFAS concentrations ranged from 3.11 to 11.7 ng/g dw (median 6.32 ng/g dw) from the textile industries, 3.26–8.74 ng/g dw (median 6.20 ng/g dw) from the metal industries, 1.53–5.71 ng/g dw (median 3.38 ng/g) from the chemical industries, and 0.346–3.48 ng/g dw (median 2.39 ng/g dw) from the electronics industries. Perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), and long chain perfluorinated carboxylic acids (PFCAs) between C9 and C12 were generally dominant in these soils. In particular, PFOS, perfluorohexane sulfonate (PFHxS), and PFCAs with ≤ C6 were more frequently found in soils from industrial complexes than from other land-use types. On the other hand, PFCAs between C7 and C12 had relatively high detection frequencies regardless of the soil type. Graphical abstract: Image 1 Highlights: In this work, 15 PFAS were analyzed in soils from various land-use types. The industrial areas had the highest concentrations of PFAS in soils. PFOS, PFDA, PFOA, PFNA, PFDoDA and PFUnDA were the predominant compounds. PFOS, PFHxS and PFCAs with ≤ C6 were frequently found in soils from industries. PFCAs (C7–C12) were frequently detected in soils regardless of the land-use type.